International law, US power : the United States' quest for legal security - Scott, Shirley V. (Cambridge : Cambridge University Press, 2012)
'Observers of the USA's attitude towards international law seem to be perpetually taken aback by its actions, whether those relate to the use of force, the International Criminal Court or human rights. This book sets out to articulate the considerable degree of continuity in the nature of US engagement with international law. International Law, US Power explains that the USA has throughout its history pursued a quest for defensive and offensive legal security and that this was a key ingredient in the rise of the USA. Although skilful strategic involvement with international law was an ingredient in the USA'winning' the Cold War, the rise of China and the growing negotiating strength of leading developing countries mean that the USA is likely to find it increasingly difficult to use the same set of techniques in the future'--
'International Law. US Power has been a number of years in the making and has benefitted from two periods of research leave from the University of New South Wales and visits to Temple University and Wooster College as well as the presentation of seminars at Macquarie University, the University of Newcastle (Australia), and the National University of Singapore. I would like to thank Jeffrey Dunoff for hosting my period of research at the Beasley School of Law, Temple University and Jeffrey Lantis for hosting my visit to the College of Wooster. Jeffrey McGee kindly invited me to present a research seminar on this material at the University of Newcastle'--
Machine generated contents note: 1. The USA quest for legal security; 2. The USA pursuit of legal security through the evolution of the international law of dispute resolution; 3. The USA pursuit of legal security through the evolving regime relating to the use of force; 4. The USA pursuit of legal security in substantive policy arenas; 5. Techniques through which the USA has reconciled its practice of legal security with the principle of sovereign equality; 6. The practice of offensive legal security in USA diplomacy; 7. The future of USA engagement with international law.
Includes bibliographical references (pages 263-273) and index.
Keywords: International and municipal law -- United States; International law -- United States; United States -- Foreign relations -- Law and legislation; Conflict of laws -- United States